1992
DOI: 10.1177/0310057x9202000410
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Dissociation Curve in the Adult Respiratory Distress Syndrome

Abstract: The oxygen tension for half saturation (P50) was determined for venous blood in thirteen patients with the adult respiratory distress syndrome undergoing intensive therapy. The mean value for P50 was found to be significantly lower than the value found in ten normal control subjects (22.9 mmHg and 26.7 mmHg respectively; t = 3.03, P< O.OJ). The extent of reduction in P50 was not related to serum phosphate level nor was it a predictor of short-term outcome. It is unlikely that the slight left-shifted oxygen-hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In similar fashion, no association between serum phosphate concentrations and the standard P50 (and by implication 2,3-DPG concentrations) was identified in the studies of Myburgh 4 or Huang 5 , nor was Myburgh able to detect an influence of haemoglobin concentration on standard P50 4 . It therefore seems unlikely that serum phosphate or blood haemoglobin concentrations are important causes of altered 2,3-DPG concentrations or P50 in the majority of critically ill patients.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In similar fashion, no association between serum phosphate concentrations and the standard P50 (and by implication 2,3-DPG concentrations) was identified in the studies of Myburgh 4 or Huang 5 , nor was Myburgh able to detect an influence of haemoglobin concentration on standard P50 4 . It therefore seems unlikely that serum phosphate or blood haemoglobin concentrations are important causes of altered 2,3-DPG concentrations or P50 in the majority of critically ill patients.…”
Section: Discussionmentioning
confidence: 74%
“…Although the authors speculated on the possibility of reduced 2,3-DPG concentrations, no measurements were made. In a similar investigation by Huang and coworkers 5 , patients with ARDS were shown to have a reduced mean standard P50 when compared with normal controls. The authors were unable to suggest a cause for this reduction.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Myburgh et al reported reduced P50 in critically ill patients 37 , whereas two recent investigations 38,39 revealed no difference in P50 compared to the healthy population. Focusing on ARDS, an Australian group demonstrated leftward shifts of the oxyhemoglobin dissociation curves 40 . In contrast, a group of Belgium ARDS patients demonstrated a rightward shifted curve 41 , which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%